Influence of temperature on the phase inversion of chlorinated polypropylene. Issue 11 (3rd January 2014) - Ma, Xiaoyang; Qiao, Zemin; Huang, Zhifeng; Jing, Xinli; Gu, Chaohui; Tang, Hanliang
ABSTRACT In this study, the maleic anhydride modified chlorinated polypropylene (MCPP) resin was emulsified by mixed ionic surfactants comprising sodium dodecyl sulfate (SDS) and sulfonated castor oil (SCO). The influence of temperature on the morphology of emulsion was studied through transitional and catastrophic inversion methods. The transitional inversion of emulsion from water‐in‐oil (W/O) to oil‐in‐water (O/W) was triggered by decreasing the temperature and the catastrophic inversion was achieved by increasing the weight fraction of water. The results of transitional and catastrophic inversion both indicated that the phase inversion of "ionic surfactant–MCPP–water" system is easier to trigger at low temperatures than at high temperatures, which could be interpreted by the thermodynamic and hydrodynamic theory. Incomplete phase inversion occurred at low temperatures when the volume of water phase was small and emulsions with small particle size and narrow particle size distribution could only be obtained at an intermediate temperature. These results are of great importance for the preparation of stable polymer emulsions in food, cosmetics and paints industry. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40325.